AN ANALYSIS OF THE APPLICATION OF S 4A OF THE WILLS ACT 7 OF 1953 WITH REGARD TO MUSLIMS MARRIED WITHIN THE SOUTH AFRICAN CONTEXT - Muneer Abduroaf (Obiter, 2022)
South African Muslims constitute a religious minority group who have been living in South Africa for almost four centuries. These persons are required in terms of their religion to ensure that their estates devolve in terms of Islamic law. One of the ways of doing this would be where a testator or testatrix drafts and executes a will stating that his or her estate must devolve in terms of the Islamic law of succession upon his or her demise and that an Islamic institution should draft an Islamic Distribution Certificate stating who his or her beneficiaries are in terms of Islamic law. This type of will could be referred to as an Islamic will. The said will must however conform to the provisions found in the Wills Act 7 of 1953 (Wills Act) in order to be deemed a valid will within the South African context. Section 4A of the Wills Act states that “[a]ny person who attests and signs a will as a witness … and the person who is the spouse of such person at the time of the execution of the will, shall be disqualified from receiving any benefit from that will.” This article looks at the application of s 4A of the Wills Act 7 of 1953 concerning Muslims married within the South African context. The scenario that is considered in this article is where Ahmad Guru (Ahmad) executes an Islamic will on 8 August 2019, with Yusuf Tuan (Yusuf) and Amina Guru (Amina) being the only witnesses thereof. Ahmad died on 9 September 2019 leaving behind a net estate of R900,000.00, a son, Omar Guru (Omar), and a daughter, Sara Guru (Sara), as his only relatives. The Islamic Distribution provides that Omar should inherit 2/3 of R900,000.00 = R600,000.00 and Sara should inherit 1/3 of R900,000.00 = R300,000.00. One of the witnesses of the Islamic will, Amina, is also the spouse of one of the beneficiaries, Omar, as provided in terms of the Islamic Distribution Certificate. This article looks at three instances of how section 4A of the Wills Act would impact the right of Omar to inherit the R600,000.00 (based on the Islamic Will and Islamic Distribution Certificate) in the event where he was, at the time of the execution of the will, (1) married to Amina in terms of Islamic law only; (2) married to Amina in terms of Islamic law as well as civil law; and (3) married to Amina in terms of civil law but divorced Amina in terms of Islamic law. The article concludes with an overall analysis of the findings and makes a recommendation as to the way forward.